Occupational injury, disease and stress in the veterinary profession - Fairnie, Helen Margaret (Curtin University, 2005)
Scant attention has been given to occupational health hazards of Australian veterinarians. This study aimed to identify the major risk factors for occupational injury and disease, emotional health and suicide rates of veterinarians. Qualitative in-depth interviews with 45 veterinarians were carried out which revealed that a significant proportion of veterinarians were both injured, stressed and had incurred zoonotic diseases. Data linkage of the names of registered veterinarians in Western Australia with four Health Department of Western Australia databases was undertaken to provide supportive statistics on the conditions identified as being important in the interviews. The results of this latter analysis were inconclusive. Therefore a self-administered questionnaire was developed, which collected quantitative data on injuries, disease, stress and risk factors from 419 veterinarians. Since the in-depth interviews had identified stress and suicide ideation as being very significant for many of those interviewed, the Kessler 10+ scale for measuring psychological distress was included in the self-administered questionnaire. The data linkage was unable to provide accurate data about numbers of deaths of veterinarians and the records of coroners in Victoria and Western Australia which provided data on 89 veterinarians, were analysed to determine suicide rates. Despite the interviews providing considerable information about rates and risk factors for injuries, disease and stress, no statistical analyses were undertaken because they provided insufficient data for quantitative analyses.Nevertheless, statistics derived from the morbidity database using data-linkage, will be useful in comparing injuries in any future studies of this type. Data collected from the self-administered questionnaire were subjected to Chi square, and non-parametric tests and logistic regression analyses using multiple imputation for missing values. Age-standardised and age-specific rates (ASR) were calculated for data on suicide in veterinarians derived from coroners' records obtained from Western Australia and Victoria using the Rates Calculator developed by Codde.' The interviews and the survey of 464 veterinarians showed that a significant proportion of veterinarians incurred injuries and zoonotic diseases, and were highly stressed and distressed. The interviews showed that a significant proportion of veterinarians expected to be injured and/or contract zoonotic diseases. It is suggested that this acceptance may, in part, account for the number of injuries that occur. Some of these injuries, especially in mixed animal veterinarians, may be attributable to poor facilities on farms and a lack of competent support in restraint of animals. There needs to be a cultural change with regard to safety if injury is to be reduced. Using the Chi-squared analyses of the survey data, injury was associated with several risk factors including being a practice owner and being in mixed animal practice, being younger and with having taken drugs such as marijuana in the past 12 months.When all these variables were input into a logistic regression model, several of these risk factors were eliminated providing only three risk factors as predictors of injury. These were: having a back injury; taking drugs in the previous 12 months; and being between 35 and 54 years of age. Having high distress levels was not a predictor for injury. Analyses of responses to the KlOi- scale in the self-administered questionnaire revealed that the proportion of highly distressed respondents was double that of the Western Australian, New South Wales and Australian general populations which supports the findings from the interviews. Logistic regression provided three predictors for distress: being less than 35 years of age, having taken drugs in the past 12 months, and having a back injury, however having other workplace injuries was not a predictor. The findings that the suicide rate in this study was about four times that of the general Australian adult population, should be of major concern and signal that there may be factors specific to the veterinary profession that account for this high rate. This study has shown that there are high levels of psychological distress in veterinarians, especially practitioners, which suggests that veterinary practice may, in itself, be a stressful occupation. However, it may also be that some individuals with a predilection for distress, are being recruited into the veterinary profession.Better selection techniques for recruiting veterinary students using an aptitude test as well as interviews, could identify those who were unsuited for becoming veterinarians or who required additional mentoring and support upon graduation. This could reduce stress, distress and suicide in the veterinary profession. Overall, 17 recommendations were made directed at improving the quality of data collection to obtain more reliable statistical outcomes, and suggesting ways of reducing injury, distress and zoonotic disease in veterinarians.